Self-Control, Binge Drinking, and Perceptions of Drinking Levels - Baker, Daniel B. (2015)
This study utilizes Gottfredson and Hirschi’s General Theory of Crime, also known as self-control theory, to determine if there is a relationship between self-control, binge drinking, and perceptions of drinking levels. The author inquires about subjects’ self-control, which should govern their tendency toward imprudent or risky behaviors. In this study, the risky behavior of interest is binge drinking. Further, the author examines the differences between college students at the beginning of the transitional phase of emerging adulthood and those at the end of that same phase. The author provides discussion of the relationship between self-control and binge drinking, the role of age relative to self-control and engaging in binge drinking, and what these findings mean for campus policies and programs. Finally, opportunities for future research are discussed